Risk of all-cause and CHD mortality in women versus men with type 2 diabetes: a systematic review and meta-analysis. Issue 4 (April 2019) - Xu, Guodong; You, Dingyun; Wong, Liping; Duan, Donghui; Kong, Fanqian; Zhang, Xiaohong; Zhao, Jinshun; Xing, Wenhua; Han, Liyuan; Li, Li
Abstract : Objective: Previous studies have shown sex-specific differences in all-cause and CHD mortality in type 2 diabetes. We performed a systematic review and meta-analysis to provide a global picture of the estimated influence of type 2 diabetes on the risk of all-cause and CHD mortality in women vs men. Methods: We systematically searched PubMed, EMBASE and Web of Science for studies published from their starting dates to Aug 7, 2018. The sex-specific hazard ratios (HRs) and their pooled ratio (women vs men) of all-cause and CHD mortality associated with type 2 diabetes were obtained through an inverse variance-weighted random-effects meta-analysis. Subgroup analyses were used to explore the potential sources of heterogeneity. Results: The 35 analyzed prospective cohort studies included 2 314 292 individuals, among whom 254 038 all-cause deaths occurred. The pooled women vs men ratio of the HRs for all-cause and CHD mortality were 1.17 (95% CI: 1.12–1.23, I 2 = 81.6%) and 1.97 (95% CI: 1.49–2.61, I 2 = 86.4%), respectively. The pooled estimate of the HR for all-cause mortality was approximately 1.30 in articles in which the duration of follow-up was longer than 10 years and 1.10 in articles in which the duration of follow-up was less than 10 years. The pooled HRs for all-cause mortality in patients with type 2 diabetes was 2.33 (95% CI: 2.02–2.69) in women and 1.91 (95% CI: 1.72–2.12) in men, compared with their healthy counterparts. Conclusions: The effect of diabetes on all-cause and CHD mortality is approximately 17 and 97% greater, respectively, for women than for men.